POLA INTEGRASI SAPI POTONG PERBIBITAN DAN TANAMAN PADA SKALA PETERNAKAN RAKYAT (KASUS DI KABUPATEN GROBOGAN) - Djoko Pramono (Caraka Tani: Journal of Sustainable Agriculture, 2008)
The animal and crop integration has long become a common practice among farmers, especially among those who breed breeding beef cattle. It is closely related to the fodder supply system that in general makes us of the agricultural by-products (e.g., dried rice stalks), and produces composts as organic fertilizer for his farming. However, the animal and crops integration is implemented in a simple way that the resulting products have not indicated an optimal sybergy. A technology introduction has been made through in-field study for 2 years (2000-2002) to improve the knowledge of the farmers of the animal and crop integrated system. The location of the in-field study is Pilang Piyung village of Toroh Subdistrict of Grobogan District and involves 40 cooperators of the members of “CF Bersemi” group. The technology introduced includes the processing of agricultural wates (e.g, rice stalks), the animals and animal wates. The data of the use of the agricultural wastes, the animal wastes and the production performance of the animals is collected before and after the implementation of the activity using survey and observation methods. The results shows that there are 6 farmers (15%) who process and store the dried rice stalks and the other 34 farmers (85%) store the stalks directly (without any processing). The animal wastes is still processed using a simple method (without probiotics). The reproductive performance of the animals is low (long breeding interval, which isi 15 to 18 months). It is evidenced that not all of the cooperators implement the introduced technology after activity. The are only 22 farmers (55%) of the 40 farmers who process and store the rice stalks, while 12 farmers (30%) of them conduct the composting process of the wastes. The breeding internal shortens into 14 to 16 months. The evaluation result shows that it is still necessary to heighten the awareness of the adoption of the technology related to the animal and crop integrated system through a follow-up.